Does news consumption affect the propensity to participate in a civil action? - Shabangu, Bruce (University of the Witwatersrand, Johannesburg, 2022)
News consumption does not always affect the propensity of citizen to engage in civil actions. This finding was a result of regression analysis of the relationship between consumption of media news and its effect on the propensity to engage in social accountability. The purpose of the research was to determine the extent to which citizens are prompted to engage in civil action by news reports containing information on poor governance outcomes such as poor government performance, corruption and the like. The finding was citizens do not participate in civil action but they do so without being influenced by news reports. The impact of this phenomena is that democracy may not be fully enforced when democratic processes are not effectively implemented. The recommendation is that there needs to be civic education for citizens and awareness created on effective participation in civil action
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management (in the field of Public and Development Management) to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Democracy; Information; Social accountability; UCTD; SDG-9: Industry, innovation and infrastructure